2020
DOI: 10.1016/j.amsu.2020.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of liver diseases in patients referred for Fibroscan: A single center experience in the Middle East

Abstract: Background Liver diseases is a worldwide etiology causing high morbidity and mortality. Fibroscan is a quick, painless examination performed in clinic or at the patient's bedside. It is used to evaluate liver status for patients with suspected liver disease prognosis. This study aims at describing the spectrum of liver diseases among patients performing Fibroscan at a tertiary care center in Lebanon. Methods This is a retrospective data collection study on patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In our study, a high percentage of patients (94.5%) were diagnosed with hepatic steatosis (CAP ≥237 dB/m). Among them, 16.6% had S1, 24.9% had S2, and 53% had S3, proportions similar to those reported in another recently published study [30]. Furthermore, in our group, the patients diagnosed with steatosis by CAP were older, more likely to associate hypertension and T2DM, with higher BMI, LSM, FIB-4 index, and NFS values than those without steatosis.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, a high percentage of patients (94.5%) were diagnosed with hepatic steatosis (CAP ≥237 dB/m). Among them, 16.6% had S1, 24.9% had S2, and 53% had S3, proportions similar to those reported in another recently published study [30]. Furthermore, in our group, the patients diagnosed with steatosis by CAP were older, more likely to associate hypertension and T2DM, with higher BMI, LSM, FIB-4 index, and NFS values than those without steatosis.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the diagnosis of alcohol-related liver disease is usually delayed as showed by Subhani et al in a recent paper from the UK where 47% of deaths secondary to alcohol-related liver disease received their first diagnosis in emergency hospital admissions [ 13 ]. In Lebanon, a single-center study in 2020 showed that alcohol-related liver disease represented 7.7% of all causes of chronic liver disease [ 14 ]. Liver disease could contribute to the accumulation of certain drugs and toxins.…”
Section: Discussionmentioning
confidence: 99%
“…The etiological spectrum of CLDs vary depending on age, research site, illness frequency, availability of diagnostic tools, physician experience and referral pattern [21].…”
Section: Discussionmentioning
confidence: 99%